Systematic Literature Review tentang Faktor-Faktor yang Mempengaruhi Pembelajaran Bahasa Inggris - Wahyu Utama (Indo Publishing, 2026)
This study aims to identify and synthesize factors influencing English language learning through a systematic literature review approach. The research analyzes empirical studies published within the last decade to determine dominant variables affecting learning outcomes and to develop a comprehensive conceptual understanding of English learning processes. The findings indicate that English language learning is shaped by the interaction of internal and external factors operating simultaneously. Internal factors, particularly learning motivation, emerge as the most influential determinant because they directly affect learners’ engagement, persistence, and use of learning strategies. Psychological variables such as self-confidence and language anxiety are also found to significantly influence learners’ performance and participation. In addition, external factors—including teaching methods, teacher quality, learning environment, and technology integration—play essential roles in shaping learning experiences. Interactive teaching approaches and strong pedagogical competence are identified as the most impactful external contributors to successful language acquisition. The review further reveals that learning outcomes cannot be explained by a single variable but rather by a multidimensional framework in which cognitive, affective, and environmental elements interact dynamically. These findings highlight the importance of adopting integrative instructional strategies that address both learner characteristics and instructional conditions. The study provides theoretical contributions by reinforcing multidimensional perspectives of language learning and practical implications for educators, institutions, and researchers seeking to enhance English language teaching effectiveness.